(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2024)
Arjuna Ksheerapaka is an Ayurvedic formulation prepared as a milk decoction of the powdered bark of Terminalia arjuna (Roxb.) Wight & Arn. It is clinically used for a variety of cardiovascular conditions. The current study investigated the efficacy of Arjuna Ksheerapaka Churna (AKC) against dyslipidemia using a preclinical model and a randomized, active-controlled clinical trial. Different groups of Sprague Dawley rats were fed with a high-fat diet (HFD) for 7 weeks, followed by 4 weeks of AKC treatment. After that, biochemical and histopathological parameters were studied with rosuvastatin as a reference standard. In the clinical study, 30 patients were randomized in 2 groups (n = 15/group) and provided with AKC 6 g/day or rosuvastatin 10 mg/day orally for 8 weeks. The body mass index, serum biochemical, and haematological parameters were studied at the baseline (start of the treatment) and endpoint (end of the treatment). In the preclinical experiment, a marked decrease in the serum total cholesterol, low-density lipoprotein (LDL), triglycerides, fasting blood glucose, and elevated high-density lipoprotein (HDL) was recorded in the AKC-treated groups compared to the vehicle control. AKC administration also decreased the serum aminotransferases level in contrast to the rosuvastatin treatment. The clinical study showed a marked reduction in triglycerides, total cholesterol, and LDL at the end of AKC treatment compared to the baseline. The effectiveness of AKC on triglycerides, total cholesterol, and LDL reduction at the endpoint was found to be equipotent to that of rosuvastatin. However, insignificant change was observed in the haematological and other biochemical parameters in both groups at the endpoint compared with the baseline. The preclinical results concluded AKC to be safer in a HFD rat model compared to rosuvastatin as it reduced the elevated serum aminotransferases level. The clinical effectiveness of AKC was found to be equipotent to rosuvastatin. Both, clinical and preclinical studies supported the therapeutic efficacy of AKC in dyslipidemia.